Faktor-Faktor Yang Mempengaruhi Sistem Drainase Yang Berkelanjutan Berbasis Partisipasi Masyarakat (Study Kasus Kawasan Jl Pancasila Kecamatan Pondok Tinggi Kota Sungai Penuh) - mulya Eka Paksi; Aswandi Aswandi; Sunarti Sunarti (Universitas Jambi, 2022)
Jl. Pancasila Pondok Tinggi District is one of the districts in Sungai Penuh city which often experiences inundation during the rainy season. In this area, the performance of the drainage system is determined by the involvement of the community. Apart from that due to the lack of government operation and maintenance costs, the drainage system is mostly managed with community participation. Therefore drainage conditions need to be considered, evaluated with a sustainable drainage system based on community participation. This research was conducted to analyze the performance level of the drainage network on Jl. Pancasila Pondok Tinggi District Sungai Penuh city, the assessment parameters include physical condition, participation and institutional conditions (in this case the community at the research location and related institutions). This research is quantitative descriptive. Data collection was carried out by distributing questionnaires to 42 respondents, interviews with questionnaires and direct surveys to the research location to collect primary data on the physical condition of the drainage network on Jl Pancasila. Data analysis was carried out by providing an assessment of the physical conditions in the field based on direct observations. Data were analyzed using the Partial Least Square (PLS) approach, using the Smart PLS 3.0 software. PLS is a variant-based Structural Equation Modeling (SEM) statistical method. The results showed that the relationship coefficient between physical aspects of the variable on the sustainability of urban drainage had a positive and significant effect, the influence of social aspects on the sustainability of drainage in total had a positive and significant effect and the institutional aspects had a positive and insignificant effect on the sustainability of urban drainage. Keywords : Physical, Social, Institutional and sustainable urban drainage aspects